A COMPARATIVE STUDY OF ANTIMICROBIAL ACTIVITY OF THE BIOACTIVE FRACTION AND PHYTOFABRICATED SILVER NANOPARTICLES OF PTEROCARPUS SANTALINOIDES L’HERIT EX DC - AJAYI, Temitayo; NWADIMKPA , Amarachukwu; ODOH, Uchenna (African Journal of Traditional, Complementary and Alternative Medicines, 2025)
Background: Recently, the use of medicinal plants for therapeutic effects has gained attention, especially in the fight against drug ineffectiveness and antimicrobial resistance. Many studies have investigated the antimicrobial activities of various parts of Ptercarpus santaliniodes but there is limited knowledge about the activity of phytofabricated silver nanoparticles of the leaf extract. Therefore, this study is aimed at comparing the antimicrobial activities of the most active fraction of P. santaliniodes L’Herit ex DC. and its phytofabricated silver nanoparticles. Materials and Methods: 500 g of pulverized dried leaves were extracted, fractionated, and investigated for antimicrobial activities using the agar diffusion method. Silver nanoparticles were phytofabricated and characterized using colour change, UV-Vis spectroscopy, and Fourier transform infrared. The percent inhibition, minimum inhibitory concentrations (MICs), minimum bactericidal concentrations (MBCs),and minimum fungicidal concentrations (MFCs) of silver nanoparticles and the most active fraction were determined. Results: Phytochemical screening showed the presence of secondary metabolites. The inhibition zone diameters of fractions were in the range of 8.5-18 mm with fraction 5 exhibiting the highest antimicrobial activity than the standard, ciprofloxacin. The brown colour and UV-Vis spectroscopy at 318 nm confirmed the formation of silver ions and O-H, O=C=O,C=H,C=O, C=C, and N-H functional groups. The phytofabricated silver nanoparticles had a higher percent inhibition compared to fraction 5, thus, a more significant antimicrobial activity. The MICs of both samples on three organisms are 0.16 mg/mL and MBC/MFCs are >1.25 mg/mL. Conclusion: The phytofabricated silver nanoparticles of Pterocarpus santaliniodes could be a template in antimicrobial drug discovery and development.